Comparison of perceptions, attitudes and performance regarding collaborative oral health care among health‐care workers. (12th June 2020) - Haresaku, Satoru; Aoki, Hisae; Kubota, Keiko; Monji, Mayumi; Miyoshi, Maki; Machishima, Kimie; Nakashima, Fuyuko; Naito, Toru
Abstract : Objective: Collaborative oral health care among health‐care workers (HCWs) is important to prevent oral and systemic diseases. The purpose of this study was to investigate the perceptions, attitudes and performance of HCWs regarding collaborative oral health care and to compare them among HCWs. Method: The subjects were dentists (DTs), dental hygienists (DHs), hospital nurses (HNs), speech–language–hearing therapists (STs) and certified care workers (CCWs) in Fukuoka Prefecture, Japan. DTs were members of the Fukuoka Dental Association, and DHs worked in dental clinics. HNs worked in hospitals without dental departments. STs and CCWs were members of professional associations. Data were collected by a mail survey. The chi‐square test and Kruskal–Wallis test were used to compare the data among HCWs. Results: A total of 119 DTs, 91 DHs, 229 HNs, 119 STs and 121 CCWs participated in this study. The total response rate was 20.6%. There were significant differences in perceptions of what should be performed as part of oral health care among HCWs. Only 20%–60% of HCWs performed collaborative oral health care, while more than 75% were willing to perform such care. Levels of collaborative oral health care with other types of professionals and positive willingness to perform such care were lower among HNs than among the other HCWs. Conclusions: It is suggested that oral health professionals should recognise the presence of differences in the perceptions, attitudes and performance among other types of HCW and try to improve these to promote interprofessional collaboration of oral health care in hospitals.